2020
DOI: 10.1108/ribs-03-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Investigating organizational factors of social response activities and their effect on corporate social performance in MNE’s subsidiaries operating in Tunisia

Abstract: Purpose This study aims to develop a conceptual model to examine the impact of four organizational factors (expatriate managers, stakeholder engagement, corporate social mission and demand management) on the social response activities and their subsequent effect on corporate social performance among subsidiaries of multinational enterprises (MNEs) in Tunisia, characterized as a small African economy. Design/methodology/approach This study uses data collected from 115 subsidiaries established in an African co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 85 publications
3
4
0
Order By: Relevance
“…These results supported the strategic effect of economically sustainable tourism marketing practices on homestay's brand equity. These outcomes are consistent with earlier studies which stated that economic sustainable reputation is an integral component of brand equity and directly affects the long-term brand equity (Cowan and Guzman, 2020; Ghezal and Khemakhem, 2020; Kumar and Christodoulopoulou, 2014; Loučanová et al , 2021) and increases the repeat visitation in RCBHs. Profit and sustainability purpose need to go hand in hand for homestays survival and prosperity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results supported the strategic effect of economically sustainable tourism marketing practices on homestay's brand equity. These outcomes are consistent with earlier studies which stated that economic sustainable reputation is an integral component of brand equity and directly affects the long-term brand equity (Cowan and Guzman, 2020; Ghezal and Khemakhem, 2020; Kumar and Christodoulopoulou, 2014; Loučanová et al , 2021) and increases the repeat visitation in RCBHs. Profit and sustainability purpose need to go hand in hand for homestays survival and prosperity.…”
Section: Discussionsupporting
confidence: 92%
“…This section discusses possible implications based on the findings of this study for both practitioners and policymakers. This research acknowledges the findings of the large majority of studies on ICT competency, sustainability tourism marketing, PSLAs and brand equity (Ali and Frew, 2014;Antoni et al, 2020;Crist ofol et al, 2021;Ghezal and Khemakhem, 2020;Gretzel et al, 2020;Kapera, 2018;Lou canov a et al, 2021;Mena et al, 2019;Tham and Sigala, 2020;Uyar et al, 2020). Moreover, the study results offer a new perspective (i.e.…”
Section: Practical Implicationssupporting
confidence: 74%
See 1 more Smart Citation
“…Mandatory public disclosure may inform consumer and investor decisions, encouraging further action (LeBaron and Rühmkorf, 2019). Respondent 6 (Australia-based consultant), who supported companies addressing slavery, explained that “some MNEs don’t realise that confronting slavery is not anti-competitive but rather pre-competitive and improves the entire sector.” From this perspective, MNEs are not isolated players in a finite competition but stakeholders in a complex social and economic arena (Ghezal and Khemakhem, 2021). Collaboration can produce genuine win-win solutions and financial gains when a longer-term view is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…An organization's SP is concerned with a commitment to adequately contributing to sustainable economic development by working closely with the organization's employees (Kotey, 2017; Sheshadri, 2015). Studies have demonstrated that organizations should keep their relationship with the families of the employees, local communities, and society to improve the living standard of the society, which eventually will improve the SP of the organizations (Ghezal & Khemakhem, 2021). Various studies have suggested that leaders of organizations must focus on enhancing sustainability initiatives to achieve the organizations' sustainable development goals.…”
Section: Theoretical Foundationmentioning
confidence: 99%